(untitled) (Journal of Ideas in Health, 2024)
Background: The Mindu dam, an open system, serves as a microbial reservoir, housing uropathogenic microorganisms like Escherichia coli. Morogoro municipality relies on the dam for water and fish. This study aimed to assess the antimicrobial susceptibility of Escherichia coli isolated from fish and water in Mindu dam. Methods: In May 2019, a cross-sectional study was conducted in Morogoro municipality. Selected antimicrobials, including ampicillin, tetracycline, cefoxitin, erythromycin, trimethoprim, gentamicin, enrofloxacin, and nalidixic acid, were tested using the disc diffusion method. E. coli ATCC 25922 served as a positive control for quality assurance during bacterial isolation. The potential source of antimicrobial contamination was identified through the multiple antibiotic resistance index. Results: Out of 148 samples, E. coli was found in 24, none in water. E. coli showed high resistance (≥50.0%) to erythromycin (62.5%), nalidixic acid (79.2%), and ampicillin (75%). Additionally, 58.0% of isolates displayed multi-drug resistance across antimicrobial classes, with a multiple antibiotic resistance index ranging from 0.00 to 0.75. Conclusion: Antimicrobial-resistant E. coli in the food chain may heighten the spread of complex urinary tract infections in the municipality. It underscores the necessity for robust municipal surveillance of antimicrobial resistance and effective antimicrobial stewardship for enhanced infection prevention and control.